1969
DOI: 10.1063/1.1670818
|View full text |Cite
|
Sign up to set email alerts
|

Deuteron Magnetic Resonance Study of Cupric Sulfate Pentahydrate

Abstract: ESR OF AS0 2 1- IN CALCITE 439 The hyperfine structure separations in the ESR spectrum of the As0 2 2-molecule-ion was examined as a function of temperature. Upon warming from 4.2° to 4000K the separation!? are observed to a decrease by approximately 10%, see Fig. 3. Measurements above 4OO 0 K were not attempted due to the onset of thermal decay of the defect center. Unlike the behavior of the CO 2 -molecule-ion in ca1cite,23 no evidence was un-covered in this ESR spectrum to suggest reorientation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
84
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(94 citation statements)
references
References 48 publications
8
84
0
Order By: Relevance
“…The splitting of the doublet clearly narrowed to 30 kHz, however, suggesting that the methyl axis now has an orientational fluctuation. In a two-site jump model, this 7-kHz narrowing requires a fluctuation of the methyl axis over an angle of +30" (Soda & Chiba, 1969). Granted that hydration induces a native conformation in SSI, the above observation suggests that smallamplitude motions are present in the side chains of methionines 70 and 73 in the S1 and/or S4 pockets of the enzyme.…”
Section: Significance Of the Internal Motions Of The Met Side Chains mentioning
confidence: 94%
“…The splitting of the doublet clearly narrowed to 30 kHz, however, suggesting that the methyl axis now has an orientational fluctuation. In a two-site jump model, this 7-kHz narrowing requires a fluctuation of the methyl axis over an angle of +30" (Soda & Chiba, 1969). Granted that hydration induces a native conformation in SSI, the above observation suggests that smallamplitude motions are present in the side chains of methionines 70 and 73 in the S1 and/or S4 pockets of the enzyme.…”
Section: Significance Of the Internal Motions Of The Met Side Chains mentioning
confidence: 94%
“…In this case, Sinnecker et al (21,22,24) have shown that the point dipole model does not work due to the increased covalent character of the H-bond that is not covered in the point dipole approximation. A more reliable alternative approach is to evaluate H-bond distances from the nuclear quadrupole coupling constant of 2 H. As empirically proposed by Soda and Chiba (25) where a and b are empirical parameters (22). Using a ϭ 319 kHz and b ϭ 607 kHz Å 3 (20) and the value of ϭ 176 Ϯ 4 kHz deduced from our work, we obtain from Equation 2 a bond length of r(O-2 H) ϭ 1.62 Ϯ 0.02 Å.…”
Section: Table 1 Hyperfine Tensors Derived From Contour Line Shape Anmentioning
confidence: 99%
“…Alternatively, the larger peak-to-peak splittings observed for the ammonium-labelled (MA),TeBr, could imply that its static value of the quadrupolar coupling constant, X , is larger than for (CD,NH,+),TeBr,. This second explanation is less likely, since it has been determined (22,23) nium groups continue. That is, the motion of the C-N axis in solid I1 is highly hindered relative to that in the solid I phase.…”
mentioning
confidence: 96%